MODEL KEPEMIMPINAN GEREJA YANG PARTNERSHIP DAN INOVATIF DALAM PENGEMBANGAN ORGANISASI PERSEKUTUAN GEREJA-GEREJA PAPUA DI PAPUA BARAT - Christian, Ferdinandus; Ramandei, Philipus; Parinussa, Sherly (Jurnal PKM Setiadharma, 2024)
The movement of an organization cannot be separated from the role of a leader. Still, an important question is what kind of leadership model is suitable to be applied in an oikoum Church organization, in this case, the Papuan Churches Association in West Papua Province. Indeed, what kind of leadership model or style is suitable for developing a complex and pluralistic religious organization such as PGGP West Papua? Can the current leadership model answer the various fundamental problems the West Papua PGGP organization faces? FGD activities get input from participants who are very enthusiastic about participating in this activity. These inputs benefit the future development of West Papua PGGP by considering the strengths, weaknesses, opportunities, and threats. The results of these inputs will provide input for the West Papua PGGP management to carry out appropriate strategies to develop the West Papua PGGP organization in the future in entering the current era of globalization.